Design of Data Transceiver Using Differential Quaternary Phase Shift Keying (DQPSK) Modulation Technique - Chuah, Khar Yee (1996)
There are few factors that contributes to the commercial failure of the Cordless Telecommunication 2nd Generation (CT2) system. Amongst those factors are the limitations and inefficiency of the system, such as cell size, bit-error-rate, throughput and bandwidth efficiency. The aim of this study is therefore to propose a modulation technique that could potentially overcome some of the above mentioned limitations. To model the system, a reliable data transceiver using Differential Quaternary Phase Shift Keying (DQPSK) modulation technique was designed and simulated using HP-EESof Microwave System Simulator called OmniSys. Two frequency spectrum, namely 1-GHz and 5-GHz, which are commonly used in cellular phones and satellite communications respectively, have been selected for analysis. However, because of the higher propagation path loss for 5-GHz, only the I-GHz system was selected for further investigation in this thesis, as a proposed frequency to improve the CT2 system. Simulations of the DQPSK transceiver at 1-GHz have shown that bit-errorrate (BER) of 10-6 or better could be achieved compared to 10-3 in CT2. This is suitable for data transceiver with a minimum receive power (Rx_PWR) of -60dBm. The coverage also improved from 200 meters (maximum radius for CT2) to 1250 meters with acceptable transmit power «35dBm). The simulation also showed that the throughput (TP> of 120 Kbitls can be achieved compared to 72 Kbitls for CT2 system and the bandwidth efficiency can be improved from 0.72 bitIHz for CT2 system to 1.46 bitIHz for the proposed system. Thus, from these simulation results, the aim of proposing a modulation technique to improve CT2 system has been achieved. The performance of the reliable data transceiver using DQPSK modulation technique operating at 1-GHz has found to be satisfactory.